Validation of a methodology to determine female white sturgeon (Acipenser transmontanus Richardson, 1836) habitat use within a riverscape during the spawning season. (17th September 2014) - Paragamian, V. L.; Rust, P.
Summary The objective was to use hydrologic and bathymetric models for the riverscape of the Kootenai River, Idaho, USA and integrate these data with radio telemetry locations of two female white Sturgeon, Acipenser transmontanus Richardson, 1836, during the spawning season. The detailed analysis of habitat features and models provided an enhanced understanding of the habitat preferences of spawning White Sturgeon, which could be used to protect or enhance the habitat. Hydrologic models will also provide a basis to incorporate a larger sample of fish in the future. The White Sturgeon habitats were studied during the 2002 and 2003 spawning seasons. Depth sensitive radio transmitters, geographic positioning systems, single‐beam and multibeam echo sounders and multidimensional surface water modeling were used to identify similarities and dissimilarities in the habitat selection of the two monitored female White Sturgeon. The movements of the two fish were not randomly distributed; both fish spent a significant amount of time swimming near the river bottom and thalweg or resting near the river bottom (within 20% of the lower water column [6–9 m]). Mahalanobis distances quantitatively described the similarities between select habitat features of depth, river velocity and riverbed slope at the studied locations and compared the entire spawning reach. The fish occupied sites previously identified as spawning locations. Both fish selected similar depth, median velocity (0.3 m s−1) and bank preferences, avoiding the shallow water on the inside of meander bends and tending to stay in the deeper water on the outside of meanders. They exhibited a tendency to occupy intermediate velocities in parts of the river where the ratio of the velocity at the fish to the maximum velocity in the channel cross‐section was >0.25 and <0.75. Some of the differences in habitat selection were likely due to the larger river discharge in 2002 compared to 2003, the length of time each fish was monitored, and the length of the spawning reach occupied by each fish. Some of the differences could, however, have been due to individual preferences. A larger sample size will greatly enhance studies.